PEMBINAAN BUDAYA LITERASI BERBASIS ANDROID UNTUK KEMAHIRAN BAHASA INGGRIS DAN KESANTUNAN BERBAHASA - Yunisa yunisa Oktavia; Emil Eka Putra; Mesri Silalahi (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Literacy culture needs to be intensified so that the public does not become prey and does not accept deceptive news that can damage the single diversity order ika. The following are discussions for the purpose of this service activity to be carried out. (1) Communities are more receptive to certain news so that conflict and hostility can easily occur between them. (2) The community does not understand literacy in order to be able to think critically and wisely. (3) The Seroja community has not yet developed android-based literacy to improve English proficiency. (4) Daily conversations need to be reflected. The method of applying this service is a service team that transfers material and practices using Android for five meetings from December 2, 2018 to February 24, 2019. A supporting team that discusses the issue of literacy culture is based on Android, using Android to use and use English applications. for English success skills. In addition, talking about important politeness in everyday life. The results of services for this community are people who are critical, change their mindset, have proficiency, English, and improve understanding of the community of intelligent vocabulary and characters. Therefore, this service is important to enhance the Android-based literacy culture to improve English proficiency and politeness through the character education of the Seroja community in Sagulung District, Batam City.